2017
DOI: 10.1302/1863-2548-11-170277
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific 3D models aid planning for triplane proximal femoral osteotomy in slipped capital femoral epiphysis

Abstract: PurposeSlipped capital femoral epiphysis (SCFE) can result in a complex three-dimensional (3D) deformity of the proximal femur. A three-plane proximal femoral osteotomy (TPFO) has been described to improve hip mechanics. The purpose of this study was to evaluate the benefits of using 3D print technology to aid in surgical planning.Patients and MethodsFifteen children treated with TPFO for symptomatic proximal femoral deformity due to SCFE were included in this study. Ten patients were treated by a single surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 22 publications
2
98
0
1
Order By: Relevance
“…Across the board, the case–control studies showed that using 3D printed models as a part of the perioperative plan showed consistent improvements in intraoperative metrics but did not significantly affect the surgical outcome. All studies which measured operating time showed a clinically significant if not statistically significant reduction in operating time compared to the control cohorts . In the studies which measured blood loss volume and fluoroscopy time, the results were similar, with most finding statistically significant reductions in these metrics (two studies showed similar levels of intraoperative blood loss).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Across the board, the case–control studies showed that using 3D printed models as a part of the perioperative plan showed consistent improvements in intraoperative metrics but did not significantly affect the surgical outcome. All studies which measured operating time showed a clinically significant if not statistically significant reduction in operating time compared to the control cohorts . In the studies which measured blood loss volume and fluoroscopy time, the results were similar, with most finding statistically significant reductions in these metrics (two studies showed similar levels of intraoperative blood loss).…”
Section: Resultsmentioning
confidence: 80%
“…While the difference in the rate of complications is reported as statistically insignificant in all cases, it is important to note these small scale studies are not adequately powered, reinforcing the need for further large scale trials to be performed. Two papers showed an observable difference in complication rate …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations